Crack pressure-bearing plugging agent and preparation method thereof
By using combined materials such as irregular aluminum alloy bridge material and polymer composite particles wrapped in phenolic resin in the plugging agent, the existing plugging agent is solved, and the effective in the deep environment is achieved Blocking and stability improvement.
Patent Information
- Application Number
- CN202411174798.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-26
- Publication Date
- 2025-01-07
AI Technical Summary
The existing leak plugging agent is not resistant to high temperature and high pressure, and cannot effectively deal with the leakage problem of cracked formations in deep, high temperature and high pressure formation environments.
Using irregular aluminum alloy bridge materials, polymer composite particles wrapped in phenolic resin, synthetic fiber materials, etc., to form a crack pressure-bearing leak plugging agent. By mixing these materials in the drilling fluid, the leak plugging agent is increased. Strength, high pressure bearing capacity and high temperature resistance.
It can effectively control the working fluid leakage of crack formations under deep, high temperature and high pressure conditions, and can adapt to the dynamic changes in the induced crack width, form a stable sealing layer, and improve the durability and sealing effect of the leak plugging agent.
Smart Images

Figure CN119264880A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plugging leaks in oil well operations, and in particular to a fracture pressure-bearing plugging agent and a preparation method thereof. Background Art
[0002] Fractured oil and gas reservoirs are widely distributed around the world, with huge reserves, and they occupy an extremely important position in the world's oil and gas exploration. Developed fractures are important seepage channels for oil and gas, which are of great significance to the efficient development of fractured oil and gas reservoirs. At the same time, the existence of fractures will also cause the loss of working fluid, which will in turn induce serious reservoir damage, restricting the efficient development of oil and gas resources. As the exploration and development moves towards deep fractured oil and gas resources, reservoir conditions such as deep wells, ultra-deep wells, and high ground stress have further increased the difficulty of controlling the loss of working fluid, and the cost and difficulty of removing or alleviating the loss damage through measures such as production increase and transformation have also increased. Effective control of working fluid loss is even more important. Using solid phase materials to plug the fracture leakage channel is the main way to control leakage. At present, conventional plugging technologies such as bridge slurry and drilling-while-drilling can no longer fully solve the actual well leakage problem on site. There are few technologies for dealing with malignant leakage caused by induced fractures, and new plugging technologies and products are urgently needed.
[0003] Induced fracture in deep fractured formations is a complex geological phenomenon involving multiple factors. It usually has the following characteristics: 1. Fracture development. Fractures are widely developed in the formation. These fractures may be naturally formed or induced by human activities (such as drilling, mining, etc.). 2. High-pressure environment. Deep formations are often in a high-pressure state. This high-pressure environment has an important influence on the stability and expansion of fractures. 3. Complex geological structure. The geological structure of deep formations is often more complex, including faults, folds and other structural forms. These structural forms have a controlling effect on the formation and expansion of fractures. For this kind of fracture, the plugging agent needs to have the ability to withstand high pressure, high temperature and high strength, so as to cope with the deep, high temperature and high pressure formation environment. The characteristic of deep induced fractures is that the fractures are formed because the wellbore is higher than the formation fracture pressure or the fracture extension pressure. Such fractures often change dynamically with the change of wellbore pressure.
[0004] The existing patent CN114525118A discloses a drilling plugging agent composition, a drilling plugging agent, and a preparation method and application thereof. The plugging agent prepared by using aluminum alloy particles, marble particles, flaky materials, fiber materials and elastic graphite with specific proportions and sizes has good pressure bearing capacity, but it is still not suitable for the plugging of induced fractures and leaks in deep fractured formations. Summary of the invention
[0005] The technical problem to be solved by the present invention is the lack of a fracture pressure-bearing plugging agent that can cope with deep, high-temperature and high-pressure formation environments.
[0006] One of the purposes is to provide a crack pressure-bearing plugging agent, which solves the problem that the existing plugging agents are not resistant to high temperature, high pressure and deep environment.
[0007] The second purpose is to provide a method for preparing the above-mentioned crack pressure-bearing plugging agent.
[0008] The present invention is achieved through the following technical solutions: A crack pressure-bearing plugging agent comprises the following raw materials in parts by weight: 4 to 25 parts of bridging material, 3 to 11 parts of filling material, 0.5 to 2 parts of deformable reinforcement material and 80 to 150 parts of drilling fluid.
[0009] As a possible design, the above-mentioned bridging material includes irregular alloy bridging materials and polymer composite particles.
[0010] As a possible design, the irregular alloy bridging material is made of aluminum alloy, and the shape of the irregular alloy bridging material is multi-faceted serrated, with a sphericity lower than 0.8 and a friction coefficient of 0.8-2.
[0011] As a possible design, the above-mentioned irregular alloy bridging material includes a primary irregular alloy bridging material, a secondary irregular alloy bridging material and / or a tertiary irregular alloy bridging material.
[0012] As a possible design, the above-mentioned first-level irregular alloy bridging material D 50 6~6.5mm, D 90 Less than 10mm, roundness is 0.4-0.45; the secondary irregular alloy bridging material D 50 3~3.2mm, D 90 The three-level irregular alloy bridging material D 50 2~2.13mm, D 90 The diameter is 2.6~2.85mm, and the roundness is 0.45~0.6.
[0013] As a possible design, the polymer composite particles are prepared by wrapping rigid calcium carbonate with a phenolic resin peritoneum.
[0014] As a possible design, the filling material includes high-strength flaky plugging material and / or high-strength calcium carbonate particles.
[0015] As a possible design, the deformed reinforcement material is a synthetic fiber material with a length-to-diameter ratio of 200-500.
[0016] As a possible design, the deformable reinforcement material includes synthetic fibers, fibers processed from minerals and / or fibers processed from plants.
[0017] The invention also provides a method for preparing the crack pressure-bearing plugging agent, which comprises adding a bridging material, a filling material and a deformable reinforcement material into the drilling fluid and mixing them evenly.
[0018] Compared with the prior art, the present invention has the following advantages and beneficial effects: When used, the present invention selects an irregular aluminum alloy as the bridging material for deep downhole leakage. Due to the regular shape and serrations, it is easier to be retained in the gap, so that a bridge can be quickly formed and a plugging layer can be efficiently formed. In addition, due to the use of deformed tie rod materials, the plugging agent has the advantages of high strength, high pressure bearing capacity and high temperature resistance, can effectively cope with deep, high temperature and high pressure formation conditions, form a stable plugging layer, and effectively control the leakage of working fluid in fractured formations. In addition, due to the excellent ductility and flexibility of the aluminum alloy, the plugging agent can adapt to the characteristics of dynamic changes in the induced crack width after plugging.
[0019] Specifically, bridging materials include irregular alloy bridging materials and polymer composite particles. Irregular alloy bridging materials have low sphericity, high friction and high toughness, and can meet the control requirements of induced crack leakage. The irregular shape can increase the friction between particles and between particles and cracks. It has good bite and can hook and lock with each other, can bridge efficiently and is not easy to damage. Polymer composite particles have high strength and strong compressive resistance. Combining irregular metals with polymer composite materials can enhance compressive resistance, bonding strength and bridging efficiency. The filling materials include high-strength sheet plugging materials and / or high-strength calcium carbonate particles. After the large-particle polymer composite material and irregular alloy bridging material form a bridging structure, the high-strength calcium carbonate particles are filled into the gaps, so that the plugging layer is denser, which can isolate the pressure between the wellbore and the formation. The high-strength sheet plugging material also plays an auxiliary bridging role. Based on the unique shape of the sheet material, it can be wedged into the tiny gaps between the particles, and it will roll due to environmental effects when entering the gap, making it easier to stay, thereby assisting the particles in bridging. At the same time, it also has a filling effect, further improving the strong plugging characteristics of the formula. The deformed tie rod material has strong dispersibility, higher aspect ratio, and density adaptability. Compared with the currently used fiber materials in the industry, it can be better mixed with other materials, assist in bridging, and cooperate with each other to further improve the efficiency and stability of the plugging layer. Compounding several materials, mixing them into the drilling fluid, and filling the gaps can effectively meet the plugging needs of deep induced cracks. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings: Figure 1 The friction coefficient diagram of the irregular alloy bridging material of Example 3; Figure 2 This is a graph showing the compressive strength test results of the polymer composite material of Example 2; Figure 3 This is a diagram of the plugging pressure bearing capacity of Example 1; Figure 4 The plugging pressure bearing capacity of Example 2 and the commercially available plugging formula (conventional plugging); Figure 5 This is a diagram of the plugging pressure bearing capacity of Example 3. DETAILED DESCRIPTION
[0021] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with examples and drawings. The illustrative embodiments of the present invention and their description are only used to explain the present invention and are not intended to limit the present invention. If specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0022] A crack pressure-bearing plugging agent comprises the following raw materials in parts by weight: 4 to 25 parts of bridging material, 3 to 11 parts of filling material, 0.5 to 2 parts of deformable reinforcement material and 80 to 150 parts of drilling fluid.
[0023] The above-mentioned drilling fluid is a conventionally used drilling fluid.
[0024] In some embodiments of the present invention, the bridging material comprises irregular alloy bridging materials and polymer composite particles.
[0025] The irregular alloy bridging material selected is aluminum alloy, which is a rigid material and has an irregular shape and low sphericity (less than 0.8), so it has good grip and adhesion. The irregular part can be embedded in the contact part to improve the overall stability. And because of its irregular shape, the contact area with the outside world will increase, which can increase friction, making it difficult to flow back after entering the crack. It has high retention capacity, and because it is an aluminum alloy, it has a certain flexibility, so it can adapt to the width changes of the induced cracks.
[0026] The polymer composite material is prepared from rigid calcium carbonate particles coated with phenolic resin. Since calcium carbonate particles have good rigidity and good compressive resistance, but may be damaged under high pressure, the phenolic resin wrapping can absorb and disperse external impact energy, improve the toughness of the material, and prevent the calcium carbonate particles from breaking under external forces. At the same time, due to the combination of phenolic resin and calcium carbonate particles, the phenolic resin on the surface can be deformed and absorb the impact when subjected to formation pressure, so that the polymer composite material has excellent compressive resistance, which makes the polymer material highly durable in cracks. In addition, since the impact and pressure will be absorbed by the phenolic resin on the surface, the polymer composite material has good stability and is not prone to overall deformation, damage, and displacement. It can be used as the skeleton particles of the plugging layer to stabilize the structure of the plugging layer.
[0027] Preferably, the mass ratio of the irregular alloy bridging material to the polymer composite particles is (2.5-3.5):1, and more preferably, the ratio is 3:1.
[0028] In some embodiments of the present invention, the irregular alloy bridging material is made of aluminum alloy, has a multi-faceted serrated shape, a sphericity lower than 0.8, and a friction coefficient of 0.8-2.
[0029] The multi-faceted serrated aluminum alloy has a high friction coefficient and low sphericity, which makes it have good retention performance in the gap and can be stably embedded in the contact gap. In addition, since the aluminum alloy has a certain flexibility, when used, even if it is an induced crack, it can adapt to the width change of the induced crack, thus having a good blocking performance.
[0030] In some embodiments of the present invention, the above-mentioned irregular alloy bridging material includes a primary irregular alloy bridging material, a secondary irregular alloy bridging material and / or a tertiary irregular alloy bridging material.
[0031] Due to the diversity of gaps in the strata, the inventors found through research that if only one type of bridging material is used, the material size may be too large, resulting in large bridging gaps and failure to form a good plug, or the material size may be too small, resulting in poor filling effect on the gaps. However, by mixing the three materials, due to the difference in material size, during filling, both the bridge can be quickly built and the bridge gap can be filled, so that the filling material is not easily lost and the filling effect of the gap is improved.
[0032] By mixing the above-mentioned first to third level irregular alloy bridging materials, the requirements of different strata can be met, thereby achieving a plugging effect of multi-level stable bridging.
[0033] Preferably, the multi-faceted serrated irregular alloy bridging material is produced by cutting and crushing.
[0034] Preferably, the weight ratio of the primary irregular alloy bridging material, the secondary irregular alloy bridging material and the tertiary irregular alloy bridging material is (1-10):(3-7):(3-7).
[0035] In some embodiments of the present invention, the material properties of the above-mentioned primary irregular alloy bridging material, secondary irregular alloy bridging material and tertiary irregular alloy bridging material are shown in Table 1.
[0036] Table 1 Leakage blocking materials <![CDATA[ D 50 (mm)]]> <![CDATA[ D 90 (mm)]]> Roundness First-class irregular alloy bridging material 6~6.5 >10 0.4~0.45 Secondary irregular alloy bridging material 3~3.2 4.1~4.3 0.4~0.43 Three-level irregular alloy bridging material 2~2.13 2.6~2.85 0.45~0.6 The above-mentioned irregular alloy bridging material D 50 It can be 6.1, 6.2, 6.4 or any other value; D 90 It can be 1, 5, 7, 6 or any other value; the roundness can be 0.41, 0.42, 4.4 or any other value.
[0037] The above-mentioned secondary irregular alloy bridging material D 50 It can be 3.1, 3.12, 3.18 or any other value; D 90 It can be 4.11, 4.15, 4.27, 4.26 or any other value; the roundness can be 0.41, 0.412, 4.24 or any other value.
[0038] The above three levels of irregular alloy bridging materials D 50 It can be 2.1, 2.02, 2.08 or any other value; D 90 It can be 2.61, 2.75, 2.67, 2.76 or any other value; the roundness can be 0.455, 0.452, 4.58 or any other value.
[0039] Preferably, the material properties of the primary irregular alloy bridging material, the secondary irregular alloy bridging material and the tertiary irregular alloy bridging material are shown in Table 2.
[0040] Table 2 Leakage blocking materials <![CDATA[ D 50 (mm)]]> <![CDATA[ D 90 (mm)]]> Roundness First-class irregular alloy bridging material 6.25 >10 0.42 Secondary irregular alloy bridging material 3.08 4.21 0.41 Three-level irregular alloy bridging material 2.06 2.72 0.53 In some embodiments of the present invention, the polymer composite particles are prepared by wrapping rigid calcium carbonate with a phenolic resin peritoneum.
[0041] Preferably, the particle size of the rigid calcium carbonate is 1 to 15 mm, and the thickness of the phenolic resin film of the polymer composite particles is 5 to 50 μm. The inventors have found that this size has the best strength, best compression resistance and good economy.
[0042] In some embodiments of the present invention, the filling material comprises a flaky plugging material and high-strength calcium carbonate particles. Preferably, the flaky plugging material can be a flaky shell.
[0043] In some embodiments of the present invention, the filling material includes high-strength flaky plugging material and / or high-strength calcium carbonate particles.
[0044] Preferably, the ratio of high-strength sheet plugging material and / or high-strength calcium carbonate particles is 1:1. The high-strength sheet-like plugging material is a sheet-like synthetic resin, and the material may be polycarbonate, a sheet-like material obtained by filling glass fiber with resin, high-density polyethylene or other materials.
[0045] The high-strength calcium carbonate particles may be calcite.
[0046] In some embodiments of the present invention, the deformed reinforcing bar material is a synthetic fiber material with an aspect ratio of 200-500.
[0047] Preferably, the aspect ratio of the deformed reinforcement material may be 250, 280, 350, 400 or other values.
[0048] The deformable reinforcement material is an organic polymer synthetic modified fiber. Compared with traditional fibers, it is modified with a surfactant (fluoride), has water-oil dual transmission, and has high dispersibility in both oil-based and water-based drilling fluids. It has a length of 0.3~13mm and an aspect ratio of more than 200:1. It has a good deformation reinforcement effect and effectively improves the stability of the plugging layer. It has a high density and can enter the cracks together with the granular material, thereby improving the ability of the drilling plugging slurry to carry the plugging material particles and has auxiliary bridging ability.
[0049] In some embodiments of the present invention, the deformable reinforcement material includes synthetic fibers, fibers processed from minerals, and / or fibers processed from plants.
[0050] The fibers obtained by processing the above plants can be cotton fibers, coconut shell fibers, hemp fibers or other fibers, which are extracted from plants and have good biodegradability and renewability. The fibers obtained by processing minerals can be glass fibers. The above synthetic fibers can be polypropylene fibers, nylon fibers or aramid fibers.
[0051] A method for preparing a crack pressure-bearing plugging agent comprises adding a bridging material, a filling material and a deformable reinforcement material into a drilling fluid and mixing them evenly.
[0052] Preferably, the above method specifically adds high-strength calcium carbonate particles, polymer composite particles, irregular alloy bridging materials and high-strength flaky plugging materials into the plugging slurry in order from small to large particle sizes, stirs evenly, and finally adds the deformed reinforcement material and mixes evenly.
[0053] Example 1
[0054] A preparation method of a crack pressure-bearing plugging agent, Raw materials: irregular alloy bridging materials (including first-level irregular alloy bridging materials, second-level irregular alloy bridging materials and third-level irregular alloy bridging materials with a weight ratio of 4:5:3, first-level irregular alloy bridging materials of 6.25mm, D 90 It is 3mm, the roundness is 0.42; Secondary irregular alloy bridge material material D 50 It is 3.08mm, D 90 The diameter of the three-level irregular alloy bridge material is 4.21mm and the roundness is 0.41. D 50 It is 2.06mm, D 90 The materials include 12kg of diamond (2.72mm in diameter and 0.53 in roundness), 4kg of polymer composite material, 3kg of high-strength sheet plugging material (polycarbonate), 3kg of high-strength calcium carbonate particles, 0.8kg of deformed reinforcement material (nylon fiber with a length-to-diameter ratio of 300) and 100kg of drilling fluid.
[0055] High-strength calcium carbonate particles, polymer composite particles, irregular alloy bridging materials and high-strength flaky plugging materials are sequentially added to the plugging slurry and stirred evenly, and finally the deformed reinforcement material is added and mixed evenly.
[0056] The compressive strength test results of the above polymer composite materials are as follows: Figure 2 The polymer composite bridging material was pressurized at 25 MPa using a hydraulic press, and the particle size distribution curve of the material before and after pressurization was obtained, see Figure 2 , polymer composite material, high strength. After the plugging material is pressurized, the particle size distribution D90 change rate is only 4.5%.
[0057] The roundness of the above irregular alloy bridging materials is calculated by the following formula: Where A is the average area of the material and P is the average perimeter of the material.
[0059] The friction coefficient of the above irregular alloy bridging material is measured by a friction coefficient measuring instrument. Figure 1 shown.
[0060] Example 2
[0061] This embodiment is basically the same as the embodiment 1, except that the irregular alloy bridging material includes a primary irregular alloy bridging material and a secondary irregular alloy bridging material. D 50 It is 6.25mm, D 90 It is 3mm, the roundness is 0.42; secondary irregular alloy bridging material D 50 It is 3.08mm, D 90 It is 4.21mm and the roundness is 0.41.
[0062] Example 3
[0063] This embodiment is basically the same as the embodiment 1, except that the irregular alloy bridging material comprises a first-level irregular alloy bridging material, the first-level irregular alloy bridging material is 6.25 mm, D 90 It is 3mm and the roundness is 0.42.
[0064] Example 4
[0065] This embodiment is basically the same as Embodiment 1, except that the raw materials include 15 kg of irregular alloy bridging material (with the same proportion as the irregular alloy bridging material in Embodiment 1), 6 kg of polymer composite material, 5 kg of high-strength sheet plugging material (polycarbonate), 5 kg of high-strength calcium carbonate particles, 0.5 kg of deformed tie rod material (nylon fiber with an aspect ratio of 300) and 80 kg of drilling fluid.
[0066] Example 5
[0067] This embodiment is basically the same as Embodiment 1, except that the raw materials include 18 kg of irregular alloy bridging material (with the same proportion as the irregular alloy bridging material in Embodiment 1), 7.2 kg of polymer composite material, 1.5 kg of high-strength sheet plugging material (polycarbonate), 1.5 kg of high-strength calcium carbonate particles, 2 kg of deformed tie rod material (nylon fiber with an aspect ratio of 300) and 150 kg of drilling fluid.
[0068] Comparative Example 1 This comparative example is basically the same as Example 1, except that the polymer composite material is made of calcium carbonate particles wrapped by polyurethane resin.
[0069] Polyurethane resin has the advantages of high strength, good heat resistance, good toughness and good chemical stability.
[0070] Comparative Example 2 This comparative example is basically the same as Example 1, except that the polymer composite material is made of microspheres formed by pressing silicon micropowder wrapped with phenolic resin.
[0071] Comparative Example 3 This comparative example is basically the same as Example 1, except that the above-mentioned irregular alloy bridging material is replaced with a square metal material of the same material. D 50 It is 6.1mm.
[0072] Comparative Example 4 This comparative example is basically the same as Example 1, except that the aspect ratio of the deformed reinforcing bar material is 100.
[0073] Comparative Example 5 This comparative example is basically the same as Example 1, except that the aspect ratio of the deformed reinforcement material is 700.
[0074] Experimental Example 1 A plugging experiment was carried out using a high-temperature and high-pressure full-diameter core fracture plugging instrument to evaluate the pressure-bearing capacity of the plugging formulas of Example 1, Example 2 and a commercially available plugging agent (Deli Petroleum Drilling Plug Agent).
[0075] The experimental test of the plugging formula mainly reflects the pressure bearing capacity of the plugging layer, the plugging formation time, the permeability of the plugging layer and the retention position of the plugging layer in the cracks. The specific operation of the test experiment is as follows: ① Experimental instruments The instrument used in this experiment is a high-temperature and high-pressure three-dimensional curved surface crack plugging instrument, which can simulate formation temperature, formation pressure, various leakage formations (including cracks and holes) and other conditions. The formation simulation module is a two-petal structure, which can adjust parameters such as crack length and height to simulate the induced crack expansion and extension behavior. After the experiment, it can be taken out and separated to observe the formation plugging situation. The high-pressure, high-acid solubility anti-leakage plugging drilling fluid formula is preferred.
[0076] ② Experimental parameters The experimental temperature is room temperature to 150°C, the flow pressure is 0 to 25 MPa, the core size is Φ105×300 mm, the fracture width is 1 to 5 mm, and the confining pressure is 0 to 90 MPa.
[0077] ③ Experimental steps Test of plugging material plugging ability: Load the simulated formation into the simulated wellbore, close the outlet valve, pour the plugging material through the simulated wellbore injection port, tighten the injection port, and stir and heat the plugging material. Inject high-pressure nitrogen into the plugging material through the pressure regulating valve to build pressure. After a certain pressure, quickly open the outlet valve to establish the plugging process. The outlet end connects the discharge port to the liquid collection box (with a lid) through a high-pressure hose to prevent liquid splashing after opening the valve; the leakage loss during the plugging process can be measured through a 30Kg electronic scale.
[0078] Test of the pressure bearing capacity of plugging materials: After the plugging process with the plugging agent of Example 1 is completed, the nitrogen gas source is turned off and the plunger pump circulation pressurization pipeline is switched. The valve at the formation outlet is kept open, and the discharge port is connected to the liquid collecting box through a high-pressure hose to prevent liquid splashing after the formation is pressed open; the amount of liquid discharged by the plugging material after the formation is pressed open can be measured by a 30Kg electronic scale. The high-pressure plunger pump continuously pumps drilling fluid or clean water into the simulated wellbore to establish a high-pressure environment, up to 30MPa, with a flow rate of 1.6L / H, and the flow rate is changed by the frequency converter.
[0079] The test results of the plugging ability of plugging materials are as follows: Figure 3-5 shown. Figure 3 The plugging pressure bearing capacity of Example 1 is above 24 MPa. Figure 4 The plugging pressure bearing capacity of Example 2 (Example 2) and a commercially available plugging formula (conventional plugging) is shown. Figure 5 This is the plugging pressure bearing capacity of Example 2 (Example 2).
[0080] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.
Claims
1. A crack pressure plugging agent, characterized in that: The invention comprises the following raw materials in parts by weight: 4 to 25 parts of bridging material, 3 to 11 parts of filling material, 0.5 to 2 parts of deformable reinforcement material and 80 to 150 parts of drilling fluid.
2. A crack pressure-bearing plugging agent according to claim 1, characterized in that: The bridging material comprises irregular alloy bridging material and polymer composite particles.
3. A crack pressure-bearing plugging agent according to claim 2, characterized in that: The irregular alloy bridging material is made of aluminum alloy, has a multi-faceted sawtooth shape, a sphericity lower than 0.8, and a friction coefficient between 0.8 and 2.
4. A crack pressure-bearing plugging agent according to claim 2 or 3, characterized in that: The irregular alloy bridging material includes a primary irregular alloy bridging material, a secondary irregular alloy bridging material and / or a tertiary irregular alloy bridging material.
5. The crack pressure-bearing plugging agent according to claim 3, characterized in that: The first-level irregular alloy bridging material D 50 6~6.5mm, D 90 Less than 10mm, roundness is 0.4-0.45; the secondary irregular alloy bridging material D 50 3~3.2mm, D 90 The three-level irregular alloy bridging material D 50 2~2.13mm, D 90 The diameter is 2.6~2.85mm, and the roundness is 0.45~0.
6.
6. A crack pressure-bearing plugging agent according to claim 2, characterized in that: The polymer composite particles are prepared by wrapping rigid calcium carbonate with a phenolic resin peritoneum.
7. The crack pressure-bearing plugging agent according to claim 1, characterized in that: The filling material includes high-strength flaky plugging material and / or high-strength calcium carbonate particles.
8. The crack pressure-bearing plugging agent according to claim 1, characterized in that: The deformed reinforcement material is a synthetic fiber material with an aspect ratio of 200-500.
9. A crack pressure-bearing plugging agent according to claim 8, characterized in that: The deformable reinforcement material includes synthetic fibers, fibers processed from minerals and / or fibers processed from plants.
10. The method for preparing a crack pressure-bearing plugging agent according to any one of claims 1 to 9, characterized in that: Add bridging materials, filling materials and deformable reinforcement materials into the drilling fluid and mix them evenly.
Citation Information
Patent Citations
Core-shell type oil-based drilling fluid plugging and bridging particle and preparation method thereof
CN107987807A
Preparation method for cross-linked polymer, modified calcium carbonate particle and plugging agent
CN110229266A
Preparation method of composite rigid plugging agent
CN112852392A
Well drilling plugging agent composition, well drilling plugging agent as well as preparation method and application of well drilling plugging agent
CN114525118A
High-temperature-resistant and high-pressure-resistant drilling fluid plugging agent
CN115322758A
Cited By
Plugging agent suitable for malignant leakage formation as well as preparation method and application of plugging agent
CN120590929A